Human Decidual NK Cells: Unique and Tightly Regulated Effector Functions in Healthy and Pathogen-Infected Pregnancies - Le Bouteiller, Philippe (Frontiers in Immunology, 2013)
NK cells present in the peripheral blood (PB) respond rapidly to pathogens or pathogen-infected cells by various means including cytotoxicity and release of cytokines and chemokines. In addition they modulate adaptive immunity via the interaction with dendritic cells. Decidual NK cells (dNK) are poorly cytotoxic in healthy pregnancy, both in humans and rodents, when compared to their PB counterparts. We will discuss recent findings that may contribute to answer the following questions: (i) Do dNK possess functional killing machinery in normal healthy pregnancy? (ii) If so, what are the regulatory mechanisms that negatively control this effector function? (iii) Have dNK from early pregnant uterus the intrinsic ability to kill pathogen-infected autologous maternal uterine cells and/or produce soluble factors that stimulate the anti-pathogen adaptive immune response? (iv) Do dNK undergo a receptor repertoire profile shift when they are in contact with pathogen-infected uterine cells? (v) Which pathogen-mediated signal(s) and molecular interactions subvert the inhibition of dNK cytolytic activity?